1988
DOI: 10.1016/0014-5793(88)81037-8
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous expression of glutamine synthetase mRNA in rat liver parenchyma revealed by in situ hybridization and Northern blot analysis of RNA from periportal and perivenous hepatocytes

Abstract: Using radiolabeled specific cDNA glutamine synthetase mRNA could be detected by in situ hybridization exclusively within those few perivenous hepatocytes which stained immunocytochemically for glutamine synthetase. This localization of glutamine synthetase mRNA was recently reported by Moorman et al. [(1988) J. Histochem. Cytochem. 36, 751-755]. Biotinylated cDNA was not suitable for mRNA detection because of a very high background staining under the conditions of in situ hybridization. Dot blot and Northern b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 23 publications
3
25
1
Order By: Relevance
“…Particular pericentral expression was also detected for glutamine synthetase (Fig. 5 c), as reported previously (41,47), and was assessed for reasons of comparison and positive zonal identification. In situ hybridization of control livers with the rat sterol 27-hydroxylase cDNA probe also showed positive staining of pericentral hepatocytes only, though the staining was far less abundant and less discrete.…”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Particular pericentral expression was also detected for glutamine synthetase (Fig. 5 c), as reported previously (41,47), and was assessed for reasons of comparison and positive zonal identification. In situ hybridization of control livers with the rat sterol 27-hydroxylase cDNA probe also showed positive staining of pericentral hepatocytes only, though the staining was far less abundant and less discrete.…”
Section: Resultsmentioning
confidence: 57%
“…1) shows the typical expression pattern for cholesterol 7a-hydroxylase in both cell preparations (mRNAs of 2.1, 3.6, and 4.0 kb, as previously reported [22,45,46]). Clearly, expression of cholesterol 7a-hydroxylase mRNA is particularly strong in the pericentral area, as is that of glutamine synthetase (two mRNAs of 1.6 and 2.8 kb, as described [47 ] 36) is expressed less abundantly in rat liver, as compared with the messengers previously described. Nevertheless, this mRNA was also localized predominantly pericentrally.…”
Section: Resultsmentioning
confidence: 81%
“…The single layer of cells around the central vein is unique in other ways. For example, these cells are the only cells in liver that possess the enzyme glutamine synthetase (Gebhardt et al, 1988). This enzyme is involved in ammonia detoxification and pH homeostasis (Haussinger et al, 1986) but it would not appear to be capable of reductively activating 2-nitroimidazole compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Proliferative potential depends on liver-specific genes and are correlated with zonal location. [20][21][22] The liver cells are organized as cell plates lined on both sides by fenestrated endothelia, lining a network of sinusoids that are contiguous with the portal and central vasculature. Recent data have indicated that the Canals of Hering, small ducts located around each of the portal triads, branch into tiny ductules that extend and splice into the liver plates throughout zone 1 forming a pattern similar to that of a bottle brush.…”
Section: The Livermentioning
confidence: 99%
“…Blood flows from the portal venules and hepatic arterioles through the sinusoids to the terminal hepatic venules and the central vein. 20,23 Gradients in the concentration of blood components, including oxygen, across the acinus, and following the direction of blood flow from the portal triads to the central vein, are responsible for some of this zonation, for example, the reciprocal compartmentation of glycolysis and gluconeogenesis. 22 In contrast to hepatocytes that occupy almost 80% of the total liver volume and perform the majority of numerous liver functions, nonparenchymal liver cells, which contribute only 6.5% to the liver volume, but 40% to the total number of liver cells, are localized in the sinusoidal compartment of the tissue.…”
Section: The Livermentioning
confidence: 99%